PENERAPAN METODE AVERAGE DALAM PENGELOLAAN PERSEDIAAN BARANG DAGANG - Sri Wahyuning; Sukemi Kamto Sudibyo; Elys Amalia (MANAJEMEN, 2024)
A well-structured accounting system also provides good benefits to the management in running their business. Every business has multiple accounting systems that are linked together and work together to achieve specific goals. Inventory is a resource that can be stored to anticipate high demand from consumers. Every company, whether trading or manufacturing, always has inventory. Without optimal inventory levels, entrepreneurs run the risk that their business will eventually no longer be able to meet their needs. the desires of consumers who need or demand the products manufactured. This can happen because products are not always available, which also means entrepreneurs lose the chance to make the profits they should. Inventory in CV. Semarang Main Aircon Center does not yet have a computerized system or is still done manually. Data storage is still in the form of notes, so it is vulnerable to corruption and makes it difficult to find information about data on specific items and the number of elements in the resume. The Main Aircon Center makes it difficult to control incoming and outgoing goods when recording inventory data, as the work is only carried out by one administrative employee. Therefore, to solve this problem, it is necessary to record inventory using a computer to facilitate data processing. By using the averaging method, the company does not have to pay attention to the utilization of inventory in the warehouse. The averaging method also makes it easier to calculate costs because there is no need to pay attention to the first or last inventory, and it is easier to use.